2013
DOI: 10.1093/jxb/ert352
|View full text |Cite
|
Sign up to set email alerts
|

A correlative microscopy approach relates microtubule behaviour, local organ geometry, and cell growth at the Arabidopsis shoot apical meristem

Abstract: Cortical microtubules (CMTs) are often aligned in a particular direction in individual cells or even in groups of cells and play a central role in the definition of growth anisotropy. How the CMTs themselves are aligned is not well known, but two hypotheses have been proposed. According to the first hypothesis, CMTs align perpendicular to the maximal growth direction, and, according to the second, CMTs align parallel to the maximal stress direction. Since both hypotheses were formulated on the basis of mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 68 publications
7
42
0
Order By: Relevance
“…A recent study showed that physical stresses in the outer periclinal wall are in a fan-like arrangement at the convex side of lobes, similar to the pattern of cortical microtubules (Sampathkumar et al, 2014). Microtubules are known to align to the direction of maximal stress and their orientation alters to match new directions of stress, for example, during development (Hamant et al, 2008;Burian et al, 2013) or after the application of pressure or wounding (Hush et al, 1990;Hush and Overall, 1991;Sampathkumar et al, 2014). Since microtubules were persistent at the same lobes during their development, it suggests the direction of stresses was maintained in the periclinal wall at the convex side of lobes from day 1 to 3.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that physical stresses in the outer periclinal wall are in a fan-like arrangement at the convex side of lobes, similar to the pattern of cortical microtubules (Sampathkumar et al, 2014). Microtubules are known to align to the direction of maximal stress and their orientation alters to match new directions of stress, for example, during development (Hamant et al, 2008;Burian et al, 2013) or after the application of pressure or wounding (Hush et al, 1990;Hush and Overall, 1991;Sampathkumar et al, 2014). Since microtubules were persistent at the same lobes during their development, it suggests the direction of stresses was maintained in the periclinal wall at the convex side of lobes from day 1 to 3.…”
Section: Discussionmentioning
confidence: 99%
“…By changing cell geometries and the parameters governing the microtubules, simulation studies have shown the plausibility of self-organization to create coaligned patterns in the absence of other information to the cell. Other investigators, most focused on apical meristems, have shown correlations between microtubule array orientation and proposed strain fields encompassing multiple cells (Heisler et al, 2010;Burian et al, 2013). These observations have led to the hypothesis that the microtubules are organized by tissue-level tensions and their resulting stress gradients across cells.…”
Section: Creating Functional Microtubule Array Patternsmentioning
confidence: 99%
“…2A,B) (Hamant et al, 2008;Sampathkumar et al, 2014). Two specific manifestations of these principles were described in the emergence of lateral roots by Amaya Vilches Barro (Maizel laboratory, University of Heidelberg, Germany) and in the generation of new organs in the shoot by Jan Traas (INRA, Lyon, France), who also integrated auxin and PIN protein localization, noting that both microtubules and PIN protein localization responded to mechanical force, but that the disassembly of highly aligned microtubule arrays was actually a requirement for symmetry breaking and the auxin-driven outgrowth of organs (Heisler et al, 2010;Burian et al, 2013).…”
Section: The Role Of Forces In Polaritymentioning
confidence: 99%